Practices of participatory museum in popular culture: Ukrainian and global contexts - Hurova, Inna (Ukrainian Cultural Studies, 2025)
Background. The participatory museum is a new phenomenon in the contemporary cultural space, shaped by the fundamental shifts in sociocultural practices and their academic conceptualizations. As the social paradigm evolves from a "culture of consumption" to a "culture of participation", today's museums are undergoing significant transformations.Objective. This study aims to analyze the phenomenon of the participatory museum as an emerging form of co-creativity within contemporary popular culture.Methods. The study employs theoretical analysis, drawing on H. Jenkins' theory of participatory culture, K. Bishop's concept of the social turn in contemporary art, N. Bourriaud's theory of relational aesthetics, and N. Simon's idea of the participatory museum. A dialectical method helps illuminate the shift in museum practices from passive artifact preservation to active audience interaction. A comparative approach underscores similarities and differences between participatory museums in Ukraine and those abroad.Results. This paper analyzes the participatory museum as a form of popular culture. It examines the influence of the social turn, relational aesthetics, and the concept of innovation democratization on the modernization of museums. It is determined that postmodern popular culture exemplifies a fundamentally new approach to creating and consuming cultural products, rooted in co-creation and active audience participation. Contemporary cultural institutions, including museums, are moving away from their traditional role as passive artifact keepers and becoming dynamic platforms for interaction, where visitors act as co-authors and meaning-makers through various forms of engagement, such as interactive exhibits, museum crowdsourcing, cultural inclusion, and gamification. Conclusions. The participatory museum, on the one hand, is a product of postmodern popular culture and, on the other, enriches popular culture through the development of innovative spaces that foster new social connections and communities, knowledge exchange, and meaning-making. Supported by digital technologies, the participatory museum stimulates the growth of popular culture, creating a multi-layered cultural reality.
Keywords: popular culture, social turn, participatory museum, gamification, museum crowdsourcing